How does the problem-oriented innovation system (PIS) help in the management of cardiovascular diseases? - Nasri, Shohreh; Amani, Javad; Safavi, Gelayol; Ghazinoory, Sepehr (Frontiers in Public Health, 2024)
Cardiovascular diseases are a multifaceted and complex problem in the health system that can change the priorities of the economic, social, and even political systems of countries. Therefore, as a grand challenge (GC), its management requires adopting a systematic, interdisciplinary, and innovative approach. In Iran, the most common causes of death, have changed from infectious and diarrheal diseases to cardiovascular diseases since 1960. Therefore, in this study, the novel framework of the problem-oriented innovation system (PIS) has been used, and cardiovascular diseases in Iran have been selected as a case study. To this end, first, the main challenges related to cardiovascular diseases in Iran were identified in two layers of "governance-centered" (including legal and policy gaps, insufficient education, financing, lack and unbalanced distribution of medical personnel) and "society driven" (including unhealthy diet and lifestyle, uncontrolled and hard-to-regulate factors, and high costs) through a library research. Then, the functional-structural framework of the problem-oriented innovation system was used to analyze cardiovascular diseases and provide policy recommendations. The findings indicate that based on the eight functions of the problem-oriented innovation system, an important part of cardiovascular diseases can be managed and controlled in three short-term, medium-term, and long-term periods. Increasing public awareness in the form of university courses, participation of the government with the private sector in building and equipping specialized cardiovascular centers, creating an electronic health record from birth, implementing a family health plan focusing on less developed areas, supporting agriculture and guaranteeing the purchase of agricultural products and healthy food, increasing the capacity of accepting students in medical and paramedical fields, and allocating pharmaceutical currency in the form of pharmaceutical subsidies directly to cardiovascular patients, are among the most important policy recommendations for this grand challenge.